2019
DOI: 10.17138/tgft(7)210-213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of <i>Leucaena leucocephala</i> for wood energy

Abstract: Poster presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Measurements of the tree height and stem diameter were conducted until the age of 12 months. At 4 months the height recorded was 0.82 m compared to the range 0.28 to 0.36 m for various breeds tested by Hendrati and Nurrohmah (2019). The recorded data showed that the largest tree had a height of 5.6 m and stem diameter of 7.9 cm.…”
Section: Growth Studymentioning
confidence: 84%
See 1 more Smart Citation
“…Measurements of the tree height and stem diameter were conducted until the age of 12 months. At 4 months the height recorded was 0.82 m compared to the range 0.28 to 0.36 m for various breeds tested by Hendrati and Nurrohmah (2019). The recorded data showed that the largest tree had a height of 5.6 m and stem diameter of 7.9 cm.…”
Section: Growth Studymentioning
confidence: 84%
“…Although L. leucocephala is highly inbred and produces copious seeds in as little as 18 months, clonal in vitro propagation would be useful as most other Leucaena species are self-incompatible and produce few inbred (true to type) seeds (Brewbaker 1982). Hendrati and Nurrohmah (2019) in their studies looked at a separating distance of 10 to 100 m in between individual mother trees (families) in an attempt to avoid or reduce in-breeding. Rapid in vitro asexual propagation techniques would also be useful for promising hybrids, such as L. pulverulenta × L. leucocephala, and L. leucocephala × L. diversifolia, that have recently been made by tedious hand pollination techniques (Brewbaker 1982).…”
Section: Growth Studymentioning
confidence: 99%
“…This program has produced superior seeds from the first generation (F1) for Calliandra callothyrsus with increment (growth) reaching 65 m 3 ha -1 year -1 , and second-generation (F2) for Acacia auriculiformis with increment can reach 72 m 3 ha -1 year -1 [70]. In the Leucaena species, preliminary observations show that the Tarramba cultivar with seeds originating from Kupang (East Nusa Tenggara Province) and known to be more resistant to pest, has tremendous biomass potential [71,72]. For Gliricidia species, the breeding is more on efforts to increase plant productivity, especially as a source of animal feed.…”
Section: Discussionmentioning
confidence: 99%
“…e species has been utilized as biofertilizer or green leaf manuring to improve soil fertility, as forage for animal feed, and a prominent source of high quality timber [8][9][10]. In Indonesia, the species has been cultivated since 1800 with some of its cultivars being recognized as important timber producers due to its valuable traits [11,12]. erefore, the species is well-adapted towards abiotic stress in marginal lands while being proved useful for afforestation and landscaping [13].…”
Section: Introductionmentioning
confidence: 99%